EMOTIONAL DIVORCE OF SECONDARY SCHOOL TEACHERS MARRIED - Lect. Dr. Hussein Mousa Abed AL_juboori (Journals Park Publishing, 2023)
The aim of the current research is to measure the emotional divorce of middle school teachers in Karbala who are married to them, and to know the significance of the statistical differences in emotional divorce according to the gender variable (male / female). Psychometric for the two scales, the researcher chose a stratified random sample consisting of (226) teachers and (263) schools, from the preparatory schools of the Directorate of Education of Karbala, and after using statistical methods, the research concluded that the teachers of Karbala governorate suffer from emotional divorce, and the results also showed that there are no differences Statistically significant in emotional divorce according to the gender variable, and in these results, the researchers presented a set of recommendations and proposals.
Keywords: Emotional divorce, school, teacher.